TraFo-CRISPR: Enhanced Genome Engineering by Transient Foamy Virus Vector-Mediated Delivery of CRISPR/Cas9 Components - Fabian Lindel; Carolin R. Dodt; Niklas Weidner; Monique Noll; Fabian Bergemann; Rayk Behrendt; Sarah Fischer; Josephine Dietrich; Marc Cartellieri; Martin V. Hamann; Dirk Lindemann (Elsevier, 2019)
The adaptation of CRISPR/Cas technology for use in mammals has revolutionized genome engineering. In particular with regard to clinical application, efficient expression of Cas9 within a narrow time frame is highly desirable to minimize the accumulation of off-target editing. We developed an effective, aptamer-independent retroviral delivery system for Cas9 mRNAs that takes advantage of a unique foamy virus (FV) capability: the efficient encapsidation and transfer of non-viral RNAs. This enabled us to create a FV vector toolbox for efficient, transient delivery (TraFo) of CRISPR/Cas9 components into different target tissues. Co-delivery of Cas9 mRNA by TraFo-Cas9 vectors in combination with retroviral, integration-deficient single guide RNA (sgRNA) expression enhanced efficacy and specificity of gene-inactivation compared with CRISPR/Cas9 lentiviral vector systems. Furthermore, separate TraFo-Cas9 delivery allowed the optional inclusion of a repair matrix for efficient gene correction or tagging as well as the addition of fluorescent negative selection markers for easy identification of off-target editing or incorrect repair events. Thus, the TraFo CRISPR toolbox represents an interesting alternative technology for gene inactivation and gene editing. Keywords: CRISPR/Cas9, genome engineering, viral vector, transient system, TraFo-Cas9, foamy virus, CAR T-cell